Estimating the urinary sodium excretion in patients with chronic kidney disease is not useful in monitoring the effects of a low-salt diet - Se-Yun Kim; Yu Ho Lee; Yang-Gyun Kim; Ju-Young Moon; Ho Jun Chin; Sejoong Kim; Dong Ki Kim; Suhnggwon Kim; Jung Hwan Park; Sung Joon Shin; Bum Soon Choi; Chun Soo Lim; et al. (The Korean Society of Nephrology, 2018)
Background : Several epidemiologic studies have suggested that the urine sodium excretion (USE) can be estimated in lieu of performing 24-hour urine collection. However, this method has not been verified in patients with chronic kidney disease (CKD) or in an interventional study. The purpose of this study was to evaluate the usefulness of estimating USE in a prospective low-salt diet education cohort (ESPECIAL). Methods : A new formula was developed on the basis of morning fasting urine samples from 228 CKD patients in the ESPECIAL cohort. This formula was compared to the previous four formulas in the prediction of 24-hour USE after treatment with olmesartan and low-salt diet education. Results : Most previously reported formulas had low predictability of the measured USE based on the ESPECIAL cohort. Only the Tanaka formula showed a small but significant bias (9.8 mEq/day, P < 0.05) with a low correlation (r = 0.34). In contrast, a new formula showed improved bias (−0.1 mEq/day) and correlation (r = 0.569) at baseline. This formula demonstrated no significant bias (−1.2 mEq/day) with the same correlation (r = 0.571) after 8 weeks of treatment with olmesartan. Intensive low-salt diet education elicited a significant decrease in the measured USE. However, none of the formulas predicted this change in the measured urine sodium after diet adjustment. Conclusion : We developed a more reliable formula for estimating the USE in CKD patients. Although estimating USE is applicable in an interventional study, it may be unsuitable for estimating the change of individual sodium intake in a low-salt intervention study.